PENGARUH MEDIA FLASH CARD DALAM PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI SD GMIT 45 MALEIPEA - Benyamin Mabilehi; Jon A. L. Yame; Yermia S. Wabang (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study was prompted by the low learning outcomes in Pancasila education among Year 4 pupils, due to teachers not utilising a variety of teaching aids. The aim of this study was to determine the effect of flashcards in Pancasila education on the learning outcomes of Year 4 pupils at GMIT 45 Maleipea Primary School. This study employed a quantitative pre-experimental design using a one-group (pre-test post-test) approach with a sample size of 21 pupils. The sampling technique used was saturation sampling. Data collection in this study was conducted via tests using a one-group pre-test post-test research design. Subsequently, a normality test was carried out, yielding a value of 0.083. Following this, a hypothesis test was conducted using a Paired Samples t-test; the data were then analysed using SPSS 22, yielding a thit of 11.206 and a ttab of 1.725. As thit > ttab, H0 was rejected and H1 accepted. From these results, it can be concluded that the use of Flash Cards as a teaching aid in Pancasila Education lessons on the topic of ‘Rights and Responsibilities at Home and at School’ at SD GMIT 45 Maleipea can improve pupils’ learning outcomes.